2012
DOI: 10.1017/thg.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Share Discordance and Umbilical Artery Doppler Change After Antenatal Betamethasone Administration in Monochorionic Twins With Selective Intrauterine Growth Restriction: Is There a Link?

Abstract: This study was designed to evaluate the degree of placenta share discordance in relation to the betamethasone-induced return of positive end-diastolic flow in monochorionic twin pregnancies with selective intrauterine growth restriction (sIUGR) and abnormal umbilical artery Doppler. Monochorionic twins with sIUGR was defined as one twin having an estimated fetal weight below the 10th percentile combined with an estimated fetal weight discordance >25%. The umbilical artery Doppler directly prior to (D0) and 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…sGR has been showed to be closely associated with impaired utero-placental perfusion [5,6]. For the non-invasive approach, previous studies evaluating utero-placental perfusion have used conventional Doppler ultrasound [6,7] to assess the umbilical artery and middle cerebral artery velocimetries. Since only severe fetal hypoxemia would result in classical abnormal Doppler velocity waveforms, mildly impaired perfusion prior to the onset of fetal compromise might not be determined in a timely manner [8].…”
Section: Introductionmentioning
confidence: 99%
“…sGR has been showed to be closely associated with impaired utero-placental perfusion [5,6]. For the non-invasive approach, previous studies evaluating utero-placental perfusion have used conventional Doppler ultrasound [6,7] to assess the umbilical artery and middle cerebral artery velocimetries. Since only severe fetal hypoxemia would result in classical abnormal Doppler velocity waveforms, mildly impaired perfusion prior to the onset of fetal compromise might not be determined in a timely manner [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound examination serves as a routine method for predicting sIUGR. Previous studies have shown that the evaluation of utero-placental perfusion indices, including umbilical artery and middle cerebral artery velocimetry using Doppler ultrasound, have good efficacy for sIUGR prediction (9)(10)(11)(12)(13)(14). Additionally, magnetic resonance imaging (MRI) of placental invasion has recently become part of clinical practice (15); however, the major disadvantages of MRI include expensive devices and relatively complex techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagic activity is upregulated by starvation, growth factor deprivation, and hypoxia . In monochorionic twin (MC) pregnancies with selective intrauterine growth restriction (sIUGR), the umbilical blood flow perfusion to the sIUGR twin is significantly decreased versus that to the appropriate‐for‐gestational age (AGA) cotwin . This poor perfusion condition is similar to starvation, growth factor deprivation, or hypoxia.…”
Section: Introductionmentioning
confidence: 99%